OPTIMASI HYDRULIC PUMP UNIT (HPU) UNTUK MENINGKATKAN LAJU PRODUKSI PADA SUMUR AGL LAPANGAN X - Albert K J Vig Nikijuluw; Tun Sriani; Roy R. Lekatompessy (Department of Mechanical Engineering, 2024)
Optimizing Hydraulic Pump Units (HPUs) is a crucial step in increasing oil production rates at the AGL well in field X. HPUs are used to lift crude oil from production wells to the surface using hydraulic pressure. This research focuses on analyzing and improving various operational aspects of HPUs to address challenges such as hydraulic leaks, component wear, and control system failures. The methods employed include preventive maintenance, the application of advanced technology for real-time monitoring, and the adjustment of operational parameters to find the optimal configuration. The study results show that with proper optimization, production rates can be significantly increased, downtime can be reduced, and equipment lifespan can be extended. Continuous monitoring and performance evaluation of HPUs after implementing optimization also provide valuable insights for further improvements. This research is expected to offer practical guidance for the oil and gas industry in implementing HPU optimization to achieve more efficient and productive operations. Keyword : pump, oil and gas, production flow rate, hydraulic pressure, AGL filed well X